Business Research: A Practical Guide for Students - Jill Collis; Roger Hussey (London Red Globe Press, 2021)
Now in its fifth edition, Business Research offers students a practical, hands-on guide throughout the research process, from literature review to writing up the results. Accessible and clear, this much loved textbook will provides the tools needed to embark on and successfully complete research projects. Its balance of practical advice, methodical approach and sound academic underpinning will gives a comprehensive grounding in research methods, so that you can decide on the most appropriate way of collecting, analysing and presenting data. New to this Edition: - Expanded practical guidance on areas students find challenging, such as sampling, writing up research and presenting data. - Fully revised and refreshed to provide a more international perspective.
Keywords: Business research; Research; Research methods; Business; Textbooks; Research Methods (BIN2044-N); (BIN3039-N) Dissertation